The evaluation of the impact of microclimatic factors on grapevine berries in a vineyard setting through molecular profiling - Du Plessis, Kari (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhDAgric)--Stellenbosch University, 2017.